The Changes in the Semantic Content of Words of Lithuanian Origin in the Process of Its Borrowing and Adoption - Дайлиденас, Р. (Kalbotyra, 1991)
Lexical and semantic analysis of words of Lithuanian origin in Old-Byelorussian business writings written within the ethnographical territory of Lithuania has shown that the most worked changes in the semantic content of lexical items can be observed in the initial stage, i.e. during the transition of the world from one language into the other.